Gene Expression Analysis with Universal n-mer Arrays - van Dam, R. Michael (Cold Spring Harbor Laboratory Press, 2002)
Gene expression profiling is one of the many applications that have benefited from the massively parallel nucleic acid detection capability of DNA microarrays. Current expression arrays, however, are expensive and inflexible. They are custom-designed for each organism and they do not offer the possibility of incorporating updated genomic information without production of a new chip. One possible solution is the development of a universal chip, consisting of all 4(n) possible DNA sequences of length n. Studying different organisms or new genes would simply require modifications to the hybridization pattern analysis software. The key problem is to find a value of n that is large enough to afford sufficient specificity, yet is small enough for practical fabrication and readout. We developed an analytical model, supported by computer-assisted calculation with yeast and mouse transcript data, to argue that it is both practical and useful to fabricate n-mer arrays with 10 ⩽ n ⩽ 16.